Protótipo de um sistema web pra gerenciamento de atividades e serviços de Assistência Técnica e Extensão Rural (ATER) na empresa Planter - MARINHO, William Freitas (2024)
This work presents the development of a prototype of a web system for managing technical assistance and rural extension (ATER) for the company Plano e Assistência Técnica Rural Ltda (PLANTER), which operates in the sector of ATER services. The main objective is to develop a prototype that assists in the process of managing activities related to technical assistance and rural extension, offering a platform for recording and monitoring the activities performed by its employees, in addition to allowing administrators to manage the existing staff and the access to the platform. To achieve this goal, methodologies widely used in software engineering were used to develop the system prototype, allowing an iterative and collaborative approach in the creation process. Through research carried out on the platforms available on the market for the area of technical assistance and rural extension, it was possible to develop a prototype that presents important differentials in relation to competitors, such as ease of use and efficiency in service management. The system prototype is intended to solve problems of processes and tasks performed manually to meet the needs of technicians who work providing ATER services, allowing the recording of data in the system, monitoring of activities carried out and control of information, ensuring the veracity of the data in the system. The clear demonstration of the usability and functionalities of the software was made possible by the developed screen prototypes. In turn, a clear understanding of the structure and behavior of the prototype PlanterSoft system was provided by the use case, activity, and sequence diagrams.